(untitled) (Cambridge, UK, 2000)
This book is a pioneering effort to delineate the various forms of informal politics within different East Asian political cultures and to develop some common theoretical principles for understanding how they work. Featured here are contributions by political scientists specializing in the regions of China, Taiwan, Japan, the Korean peninsula, and Vietnam.
Keywords: Political culture,Văn hóa chính trị; East Asia,Đông Á